A Method of Selecting Automated Driving Service Sections Considering Spatial Influence Factors - Tagyoung Kim; Kyeong-pyo Kang (Applied Sciences)
Currently, the level of automated driving technology is level 3 service in Korea, and the level 4 service has been launched overseas and is reaching the stage of commercialization. For commercialization, it is necessary not only to stabilize automated driving technology but also to prepare for service applications. To apply and expand automated driving services, it is most urgent to secure the safety of automated driving technology, and it is necessary to prepare for efficient procedures and methods suitable for automated driving services. In this study, considering the two aspects of AV manufacturer and service provider, the spatial factors affecting the safety of ADS are estimated using disengagement information in the level 3 service field data in Korea, and the method is proposed to select the automated driving service sections using spatial information analysis. To validate the method, the matching rate is compared and analyzed by applying it to the other testbed, which is currently being prepared for the level 4 car sharing service. According to validation results, it judged that the proposed method could be used to select the automated driving service section efficiently in the planning stage before deploying AVs and providing services.